Poids, santé générale et santé mentale : la situation de divers sous-groupes d'immigrants au Canada - Bergeron, Pascale; Auger, Nathalie; Hamel, Denis (Revue canadienne de santé publique, 2009)
Contexte Au Canada, l’immigrant récent est souvent en meilleure santé que le non-immigrant. L’état de santé des sous-groupes d’immigrants (ethniques, culturels, linguistiques) est moins bien connu. Méthode En utilisant des données de l’Enquête sur la santé dans les collectivités canadiennes 2005 (Cycle 3.1), les associations entre trois caractéristiques des immigrants (1-temps écoulé depuis l’immigration, 2-être une minorité visible, 3-parler une langue officielle) et trois indicateurs de santé (1-santé générale perçue, 2-santé mentale perçue, 3-indice de masse corporelle (IMC)) ont été modélisées à l’aide de régressions logistiques multiples pour les immigrants des régions métropolitaines de recensement de Montréal, Toronto et Vancouver. Elles ont été ajustées pour des facteurs sociodémographiques. Résultats Les immigrants récemment arrivés qui appartiennent à une minorité visible sont moins susceptibles d’avoir une mauvaise santé perçue, tant générale (RC 0,72; IC95 % 0,54–0,97) que mentale (RC 0,64; IC95 % 0,43–0,96) et un IMC≥25 (RC 0,51; IC95 % 0,43–0,61) que les non-immigrants. Ceux qui n’appartiennent pas à une minorité visible ne présentent pas ces associations. Les immigrants qui ne parlent pas une langue officielle sont plus susceptibles d’avoir une mauvaise santé générale perçue (RC 1,49; IC95 % 1,06–2,10) que les non-immigrants. À Toronto et Vancouver, les immigrants tendent à être associés à un IMC moindre que les non-immigrants alors que ce n’est pas le cas à Montréal. Conclusion Cette étude témoigne de la présence du phénomène de l’immigrant en bonne santé au Canada mais démontre qu’une grande variabilité existe entre les sous-groupes d’immigrants. Ces constats sont importants pour une planification adéquate des services aux immigrants.

Multilingualism (but not always bilingualism) delays the onset of Alzheimer disease: Evidence from a bilingual community - Chertkow, Howard; Whitehead, Victor; Phillips, Natalie; Wolfson, Christina; Atherton, Julie; Bergman, Howard (Alzheimer Disease and Associated Disorders, 2010)
A recent paper by Bialystok et al in Neuropsychologia (vol. 45, pgs. 459 to 464) suggested that early bilingualism produced a statistically significant 4.1-year delay in onset of memory loss symptoms in older individuals with Alzheimer disease, possibly reflecting an increase in the cognitive reserve of these individuals. That study focused on multilingual elderly patients of whom 90% were immigrants. Our memory clinic, in Montreal Canada, has the advantage of having a large set of individuals who are either multilingual immigrants to Canada, or who are nonimmigrants but raised in both official languages of Canada—French and English. We thus attempted to replicate the above findings using a larger cohort in a different setting. We examined age at diagnosis of Alzheimer disease and age at symptom onset for all unilingual versus multilingual participants, and then for those who were nonimmigrant English/French bilinguals. Overall, we found a small but significant protective effect of more than 2 languages spoken, but we found no significant benefit in bilinguals overall in relation to age at diagnosis or age at symptom onset. However, in the immigrant group, the results mirrored those of Bialystok et al with 2 or more languages delaying the diagnosis of Alzheimer disease by almost 5 years. A trend toward the same effect was also seen in nonimmigrants whose first language was French. In contrast, in nonimmigrants whose first language was English, no such effect was found. These results are discussed in relation to the earlier findings and the theory of cognitive reserve.

Providers of language-appropriate health care providers are scarce: Self-declared language capabilities of the healthcare workforce in Ontario - Demers, Chantal; Bourgeault, Ivy Lynn; Leal, Andrew; Simkin, Sarah; Sweetman, Arthur

English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistics Canada, 2017)

Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistique Canada, 2017)

Linguistic mortality gradients in Quebec and the role of migrant composition - Lo, Ernest; Tu, Mai Thanh; Trempe, Normand; Auger, Nathalie (Canadian Journal of Public Health, 2018)
Objective Anglophones and Allophones in Quebec (Canada) have lower mortality than Francophones, despite being linguistic minorities. This study assesses whether (1) language is a risk factor for mortality after accounting for migrant composition and (2) interprovincial migrants differ in mortality with respect to Quebec-born individuals. Methods We analyzed death records between 2004 and 2008 from Quebec (all-cause and main causes) and population data from the 2006 census to estimate age-adjusted mortality rates according to language and migrant status. Risk ratios by language and migrant status, adjusted for age, sex, and socioeconomic status, were estimated using Poisson generalized estimating equations. Results Francophone Quebec-borns had the highest mortality. Among Quebec-borns, Anglophones [RR= 0.85, 95% CI (0.79–0.91)] and Allophones [RR = 0.16, 95 %CI (0.12–0.22)] had lower mortality relative to Francophones. Interprovincial migrants had lower mortality (Anglophones [RR = 0.58, 95% CI (0.53–0.63)], Francophones [RR = 0.55, 95% CI (0.50–0.60)]) relative to Francophone Quebec-borns (Allophones were excluded due to small sample size). Among immigrants, mortality was lower for Francophones [RR = 0.62, 95% CI (0.57–0.67] and Allophones [RR = 0.35, 95% CI (0.31–0.38], but not Anglophones [RR = 0.92, 95% CI (0.84–1.01)], relative to Francophone Quebec-borns. Conclusion In Quebec, linguistic disparities in mortality remained after accounting for migrant status, and both Francophone and Anglophone interprovincial migrants in Quebec had lower mortality than Quebec-born Francophones. Public health initiatives to reduce linguistic disparities in health should account for migrant status.

Misinterpretation: Language proficiency, recent immigrants, and global health disparities - Pottie, Kevin (Canadian Family Physician, 2007)

Language proficiency, gender and self-reported health: An analysis of the first two waves of the longitudinal survey of immigrants to Canada - Pottie, Kevin; Ng, Edward; Spitzer, Denise; Mohammed, Alia; Glazier, Richard (Canadian Journal of Public Health, 2008)
Background Most immigrants to Canada now come from Asia, the Middle East, the Caribbean and Africa, where cultures and languages often differ significantly from the Canadian context. Subgroups of immigrants experience disparities in health. Inability to communicate in an official language in Canada may be a marker of risk for poor health due to both pre- and post-migration factors. We aimed to study the relationship between language proficiency and self-reported health. Methods We conducted a cross-sectional analysis of the first two surveys of the Longitudinal Survey of Immigrants to Canada (2001, 2003), a population-based cohort study of new immigrants to Canada. Specifically, we used logistic regression analyses to examine the relationship between self-reported health and language proficiency by sex, controlling for a range of health determinants at 6 months (wave 1) and 2 years (wave 2) after arrival. Results After controlling for covariates (age, sex, education, region of birth, immigrant class, job satisfaction, access to health care), analysis of the wave 1 survey showed that poor proficiency in English or French is significantly related to the self-reported poor health (OR=2.0, p<0.01). And this relationship was consistent in the wave 2 survey (OR=1.9, p<0.01). We also found that this statistically significant association between poor language proficiency and self-reported health holds only for women (wave 1 survey OR=2.6, p <0.01, wave 2 survey OR=2.2, p<0.01), not for men. Conclusion The association between poor language proficiency and poor self-reported health, and particularly its significantly greater impact on women, has implications for language training, health care and social services, and health information.

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Potential for patient-physician language discordance in Ontario - Sears, Jennifer; Khan, Kamran; Ardern, Chris . I.; Tamim, Hala (BMC Health Services Research, 2013)
Background Patient-Physician language discordance occurs when the patient and physician lack proficiency in the same language(s). Previous literature suggests language discordant clinical encounters compromise patient quality of care and health outcomes. The objective of this study was to quantify and visualize the linguistic and spatial mismatch between Ontario’s population not proficient in English or French but proficient in one of the top five non-official languages and the physicians who are proficient in the same non-official language. Methods Using data from the 2006 Canadian census and the 2006 Canadian Medical Directory, we determined the number of non-English/non-French (NENF) speaking individuals and the number of Ontario physicians proficient in the top five non-official languages in each census division (CD) of Ontario. For each non-official language, we produced bi-variate choropleth maps of Ontario, broken down into the 49 CDs, to determine which CDs had the highest risk of language discordant clinical encounters. Results According to the 2006 Canadian census, the top five non-official languages spoken by Ontario’s NENF population were: Chinese, Italian, Punjabi, Portuguese and Spanish. For each of the top five non-official languages, there were at least 5 census divisions with a NENF population speaking a non-official language without any primary care physicians proficient in that non-official language. The size of NENF populations within these CDs ranged from 10 individuals to 1,470 individuals. Conclusions Understanding the linguistic capabilities of Ontario’s immigrant population & the linguistic capabilities of Ontario’s primary care physicians is essential to ensure equal access and quality of healthcare. As immigration continues to increase, we may find that the linguistic needs of Ontario’s immigrant population diverge from the linguistic capabilities of Ontario’s primary care physicians. Further research on the language discordance in Ontario is needed in order to reduce the risk of language discordant clinical encounters and the negative health outcomes associated with these encounters.

Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, M.; Auger, Marianne (Institut national de santé publique du Québec, 2018)

Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, Marianne; Auger, Nathalie (Institut national de santé publique du Québec, 2018)

Health profile of linguistic communities in Québec - Tu, Mai. Thanh; Lussier, Marie-Hélène.; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)

Portrait de santé des communautés linguistiques du Québec - Tu, Mai Thanh; Lussier, Marie-Hélène; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.